Rethink Strategies in Legal Protection of Traditional Knowledge - A Case Study of Thailand - Thathong, Sun (วารสารกระบวนการยุติธรรม, 2009)
Abstract: This paper attempts to analyse Thailand's current strategies in protecting its traditional knowledge (TK) and biological resoureces. It will question how adequate the existing regime is, while seeking to highlight the various discrepancies within the system. It will reassess not only the definition of TK, but also the objectives of protection. Ultimately, this paper thus attempts to provide workable solutions to resolve the cracks and fissures of the present system in the search for an optimal strategy.